1998
DOI: 10.1300/j082v36n01_05
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Aspects of Homonegativity

Abstract: The prevalence of anti-gay violence is a widespread problem calling for thorough study and effective solutions. Hudson and Ricketts (1980) viewed homonegativity as composed of cognitive, affective, and behavioral aspects. Patel (1989) developed the Self Report of Behavior Scale (SBS) to measure respondents' previous negative behaviors toward gay individuals. Other research using this scale has yielded useful information, and further study is needed to refine the now-evolved scale (SBS-R). Participants in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 12 publications
(16 reference statements)
3
60
0
3
Order By: Relevance
“…Survey-based studies have demonstrated a positive association between sexual prejudice and self-reported past aggressive behavior toward gay men [Franklin, 2000;Patel et al, 1995;Roderick et al, 1998]. Laboratory-based studies have shown that sexually prejudiced men displayed higher levels of aggressive behavior toward a gay male, relative to the heterosexual male, but only after exposure to sexual violations of the traditional male gender role (i.e.…”
Section: Theories Of Antigay Aggressionmentioning
confidence: 99%
“…Survey-based studies have demonstrated a positive association between sexual prejudice and self-reported past aggressive behavior toward gay men [Franklin, 2000;Patel et al, 1995;Roderick et al, 1998]. Laboratory-based studies have shown that sexually prejudiced men displayed higher levels of aggressive behavior toward a gay male, relative to the heterosexual male, but only after exposure to sexual violations of the traditional male gender role (i.e.…”
Section: Theories Of Antigay Aggressionmentioning
confidence: 99%
“…Daar behoort onderskei te word tussen 'n persoon wat 'n neutrale houding teenoor homoseksuele persone inneem en 'n persoon wat in 'n homofobies-ideologiese groep met 'n homonegatiewe houding. 'n Homonegatiewe houding is vir Herek (2007:5) 'n term wat ook vir die internalisering van heteroseksisme gebruik kan word, 20 alhoewel ander navorsers soos Mayfield (2001:53-76) en Roderick et al (1998) hierdie term as 'n sinoniem vir 'n homofobiese houding, wat bestudeerbare, kognitiewe, affektiewe en gedragspatrone toon, gebruik.…”
Section: Manifestasies Van Homofobieunclassified
“…sigbare irritasie) en gedragspatrone (soos byvoorbeeld geweldadige optrede) wees (cf. Roderick et al 1998). So 'n geïnternaliseerde antigay houding van 'n homoseksuele persoon kan dan as 'n kognitiewe weersin in die gedeelde identiteit met ander homoseksuele persone beskou word.…”
unclassified
“…Algunos autores proponen que lo más acertado sería el uso de homonegatividad u homonegativismo (término utilizado en el presente estudio). La homonegatividad combina cogniciones, afectos y conductas de carácter negativo hacia las personas homosexuales o quienes socialmente parecen serlo, contemplando creencias prejuiciosas, reacciones emocionales y conductas de estigmatización (Hudson & Ricketts, 1980;Roderick, McCammon, Long & Allred, 1998;Currie, Cunningham & Findlay, 2004, Morrison & Morrison, 2011. El uso de homonegatividad, parece más acorde a la realidad actual y evitaría la relación con una fobia clínica (Wrench, 2005), aunque el uso popular y académico del término homofobia aun persiste (Bhugra, 1987;Dermer, Smith & Barto, 2010).…”
Section: Introductionunclassified